Patient experience after kidney transplant: a conceptual framework of treatment burden - Elizabeth C. Lorenz; Jason S. Egginton; Mark D. Stegall; Andrea L. Cheville; Raymond L. Heilman; Sumi Sukumaran Nair; Martin L. Mai; David T. Eton (SpringerOpen, 2019)
Abstract Background Kidney transplant recipients face a lifelong regimen of medications, health monitoring and medical appointments. This work involved in managing one's health and its impact on well-being are referred to as treatment burden. Excessive treatment burden can adversely impact adherence and quality of life. The aim of this study was to develop a conceptual framework of treatment burden after kidney transplantation. Qualitative interviews were conducted with kidney transplant recipients (n = 27) from three Mayo Clinic transplant centers. A semi-structured interview guide originally developed in patients with chronic conditions and tailored to the context of kidney transplantation was utilized. Themes of treatment burden after kidney transplantation were confirmed in two focus groups (n = 16). Results Analyses confirmed three main themes of treatment burden after kidney transplantation: 1) work patients must do to care for their health (e.g., attending medical appointments, taking medications), 2) challenges/stressors that exacerbate felt burden (e.g., financial concerns, health system obstacles) 3) impacts of burden (e.g., role/social activity limitations). Conclusions Patients describe a significant amount of work involved in caring for their kidney transplants. This work is exacerbated by individual, interpersonal and system-related factors. The framework will be used as a foundation for a patient-reported measure of treatment burden to promote better care after kidney transplantation.